2022
DOI: 10.1002/anie.202203903
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Inter‐ and Intra‐crystal Diversity of Surface Barriers in Zeolites on Mass Transport by Using Super‐Resolution Microimaging of Time‐Resolved Guest Profiles

Abstract: The applications of nanoporous crystalline materials are closely related to the mass transfer of guest molecules. However, the fundamental knowledge of mass transfer, and in particular the surface barriers controlled by the permeation of guest molecules through the external surfaces of materials, is still incomplete. The diversity of surface permeability at the single‐crystal level, caused by the varying origins of surface transport resistance, hinders the rational materials design and needs better understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…They discovered a noticeable jump in boundary concentration compared with the equilibrium value, thus indicating the influence of external surface barriers. 20,29 In comparison, the equilibrium value is quickly achieved after a quite short time interval in the absence of notable external surface barriers, as shown in Fig. 7(B).…”
Section: External Surface Barriersmentioning
confidence: 86%
See 3 more Smart Citations
“…They discovered a noticeable jump in boundary concentration compared with the equilibrium value, thus indicating the influence of external surface barriers. 20,29 In comparison, the equilibrium value is quickly achieved after a quite short time interval in the absence of notable external surface barriers, as shown in Fig. 7(B).…”
Section: External Surface Barriersmentioning
confidence: 86%
“…Recently, single-molecule fluorescence imaging has been developed as a technique to reveal spatiotemporal gradients of product molecules in zeolite crystals. 26,29…”
Section: External Surface Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, significant studies have been dedicated to the crystal surface microenvironment, such as external acidity or surface barriers, through surface modification methods. On the one hand, previous studies, such as chemical liquid/vapor deposition, phosphorus modification, and epitaxial growth, focused on the effect of external acidity without considering the surface barriers resulting from surface passivation and concluded that reducing external acidity can prevent side reactions and external coke deposition. On the other hand, modulating surface barriers allows for the regulation of the reactant and product mass transfer through the crystal surface, hence regulating the catalytic efficacy regardless of the changes of external acidity. However, it can be concluded easily that even the trivial changes of acidity should be resulted in changing surface barriers and vice versa. Since the complex interrelations between external acidity and surface barriers, independently investigating the effects of surface barriers and external acidity on the production of aromatics over zeolite continues to be an open challenge.…”
Section: Introductionmentioning
confidence: 99%